2006
DOI: 10.1111/j.1528-1167.2006.00623.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonconvulsive Status Epilepticus in Children: Clinical and EEG Characteristics

Abstract: Summary:Background: Nonconvulsive status epilepticus (NCSE) is a highly heterogeneous clinical condition that is understudied in the pediatric population.Objective: To analyze the epidemiological, clinical, and electroencephalograpic features in pediatric patients with NCSE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
85
1
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(104 citation statements)
references
References 17 publications
(24 reference statements)
8
85
1
10
Order By: Relevance
“…Retrospective studies have demonstrated NCS or NCSE in 14% to 39% of children who underwent long-term EEG monitoring in PICU or emergency departments for a variety of etiologies of acute encephalopathies. 6,7,9,10 Retrospective studies may not identify all patients who had seizures, because not all patients underwent EEG monitoring. The current study may have identified a higher incidence of seizures because EEG was performed prospectively on all children undergoing TH.…”
Section: Figure Background Evolution and Seizure Occurrence By Subjectmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective studies have demonstrated NCS or NCSE in 14% to 39% of children who underwent long-term EEG monitoring in PICU or emergency departments for a variety of etiologies of acute encephalopathies. 6,7,9,10 Retrospective studies may not identify all patients who had seizures, because not all patients underwent EEG monitoring. The current study may have identified a higher incidence of seizures because EEG was performed prospectively on all children undergoing TH.…”
Section: Figure Background Evolution and Seizure Occurrence By Subjectmentioning
confidence: 99%
“…[6][7][8][9][10][11] Further, patients treated with TH may require pharmacologic paralysis to manage shivering, clinically masking all electrographic seizures. Consequently, EEG monitoring is required for seizure detection.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] The majority of electrographic seizures were not accompanied by any clinical signs, 1,3,8,[10][11][12][13][14] even in nonparalyzed patients. 1,14 Therefore, accurate seizure identification requires CEEG.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] This variability is likely due to the smaller size of these cohorts, variability in case mix across institutions, and interinstitution variability in CEEG indications. Furthermore, previous studies were performed over nearly a decade, during which CEEG indications and other components of critical care have evolved.…”
mentioning
confidence: 99%
“…Several retrospective studies that describe findings in pediatric patients who have undergone cEEG monitoring have been published [144,[148][149][150][151][152][153]. The clinical characteristics of the patients vary and include patients being monitored following clinical seizures and patients with changes in mental status without overt seizure activity.…”
Section: Neuromonitoring and Neuroprotection In The Picumentioning
confidence: 99%